Are interregional wage differentials in Russia compensative? - Aleksey Oshchepkov (Deutsches Institut für Wirtschaftsforschung (DIW), 2007)
Interregional differentials in nominal wages in the Russian Federation are huge compared to other countries. Using the NOBUS micro-data and a methodology based on the estimation of the wage equation augmented by aggregate regional characteristics, we show that these differentials have a compensative nature. Russian workers receive wage compensations for living in regions with a higher price level and worse non-pecuniary characteristics, such as a relatively low life expectancy, a high level of air pollution, poor medical services and a colder climate. After adjusting for these regional characteristics, the relative ranking of regions in terms of average wages changes considerably. Moreover, regional nominal wages become positively correlated with interregional migration flows. According to our estimates, half of the interregional wage variation between workers with similar productive characteristics should be considered to be compensative. These results support the view that the best policy reaction to the current high interregional wage differentials should be the removal of migration barriers and a reduction in migration costs. In general, our results show that wage compensations for regional disamenities along with differences in employment composition are able to account for about three fourths of the observed interregional variation in wages.
Keywords: J3; J6; P2; R1; R2; 330; compensating differentials; regional wages; wage equation; interregional migration; transition; Russia; Regionale Lohnstruktur; Regionale Disparität; Binnenwanderung; Übergangswirtschaft; Lebensqualität; Russland